1
$\begingroup$

I am trying to derive the closed form of the sum $\sum\limits_{i=2}^n \frac{1}{i(i-1)}$ which Mathematica tells me is $\frac{n-1}{n}$. I am completely baffled on how to arrive at this result. The furthest I can get is $\sum\limits_{i=2}^n \frac{1}{i - 1} - \sum\limits_{i=2}^n \frac{1}{i}$. Is there a different way I should approach this? Any guidance would be greatly appreciated.

Context: I'm trying to prove via induction that $\sum\limits_{i=2}^n \frac{1}{i(i-1)} < 1$ for all $n \geq 2$. I can't figure out an alternate way to prove this without a closed form for the sum.

$\endgroup$
  • $\begingroup$ suggest you write out the calculation, by hand and putting fractions into lowest terms, for $n=3,$ then $n=4,$ then $n=5.$ Should be less baffling by then. $\endgroup$ – Will Jagy Oct 28 '14 at 17:44
3
$\begingroup$

Hint: You are on the right track and are almost there. If you reindex the second sum, giving $$\sum_{i=2}^n \frac{1}{i} = \sum_{j=3}^{n+1} \frac{1}{j-1},$$ do you see how the sums collapse?

$\endgroup$
3
$\begingroup$

$\frac{1}{2\times 1}+\frac{1}{3\times 2}+...+\frac{1}{n\times (n-1)}$

$=(1-\frac12)+(\frac12-\frac13)+...+(\frac{1}{n-1}-\frac{1}{n})$

$=1+(-\frac12+\frac12)+(-\frac13+\frac13)+...+(-\frac{1}{n-1}+\frac{1}{n-1})-\frac1n$

$=1-\frac{1}{n}$

$=\frac{n-1}{n}$

$\endgroup$
2
$\begingroup$

Hint: Most of the terms in $\sum_{i=2}^n 1/(i-1)$ and $\sum_{i=2}^n 1/i$ are the same. Write out a few examples for small $n$ and you'll see how it works.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.